Magnetic properties and domain structure of CoFeB/Pd multilayers with perpendicular magnetic anisotropy - Truong, Quach Duy (Vietnam Journal of Science and Technology, 2019)
The magnetic properties and domain structure of (CoFeB/Pd)n (n = 2 – 10) multilayers with perpendicular magnetic anisotropy have been investigated systematically. The study has been carried out by using vibration sample magnetometer (VSM) and magneto-optical Kerr effect (MOKE) microscope. The results show clear changes of magnetic hysteresis and domain structure when increasing the number of bilayer (n) from 2 to 10. With increasing the number of bilayer, the multilayers’ hysteresis loops change from square-shaped to slanted, while domain structures change from circular-like to maze